Techno-economic assessment of municipal solid waste gasification for electricity generation: a case study of Kampala City, Uganda - Kivumbi, Bernard; Olwa, Joseph; Martin, Andrew; Menya, Emmanuel (CIGR Journal, 2015)
This study was aimed at assessing the techno-economic potential of municipal solid waste (MSW) generated in Kampala City for electricity production through gasification. The quantity, characteristics and gasification parameters were determined. In addition, the gasifier- engine system components were sized, and an economic analysis was conducted to obtain the net present value (NPV) and the payback period. This study found that 523 t/d of MSW is collected in Kampala City. The biomass component of MSW was found to be 459.5 t/d with moisture content of 71.09% on as-received basis. The physical characteristics of the gasified biomass included 11.8% moisture content, 88.2% total solids, 25.9% ash content and 57.7 kg/m3 bulk density. The resulting normalized producer gas constituted 11.64% H2, 13.70% CO, 16.09% CO2, 54.12% N2, 4.45% CH4 and lower heating value (LHV) of 4.75 MJ/Nm3. The design fuel flow rate of 0.23 kg/s, specific gasification rate (SGR) of 5089.29 kg h-1 m-2 and specific energy demand of 42.75 GJ m-2 h-1 were obtained. This yields a net electrical power output of 425.17 kW with an overall efficiency of 15.6%. The net annual electricity generation from a single gasifier-engine system was found to be 2.97 GWh/a. The economic analysis for this system worth $887 333 of investment cost yielded a payback period of 6.57 years while the NPV at 6% interest rate was found to be nine years with a value of $316 47.
Keywords: Municipal solid waste; Biomass; Gasification; Economic analysis; Producer gas; Electricity